Population Ageing and Intergenerational Conflict: A Post-Keynesian View - William A. Jackson (Journal of Economic Studies, 1992)
Population ageing has been seen as creating economic problems often described as a worsening intergenerational conflict for resources. A rising dependency ratio is said to increase the 'burden' on the working population by forcing sacrifices in their consumption. Such apparently intuitive ideas are based on the assumption of a binding aggregate resource constraint, as would occur if resources were fully utilised. From a post-Keynesian perspective, however, unemployment and excess capacity are normal to the functioning of capitalist economies, and resources are not in general fully utilised. This paper argues that the Keynesian process of national income determination precludes any immediate relationship between population ageing and the 'burden' imposed on income recipients. Below full employment, a rising dependency ratio is not guaranteed to reduce the expenditure share of income recipients or raise their tax rates. An exclusive emphasis on intergenerational conflict can give a misleading impression of the consequences of population ageing.
Keywords: D64; E12; E24; J11; J14; 330; population ageing; dependency ratio; intergenerational conflict; taxation; Keynesian economics